2013
DOI: 10.1038/nphys2760
|View full text |Cite
|
Sign up to set email alerts
|

Unusual stable trapping of the ultrarelativistic electrons in the Van Allen radiation belts

Abstract: Radiation in space was the first discovery of the space age. Earth's radiation belts consist of energetic particles that are trapped by the geomagnetic field and encircle the planet 1. The electron radiation belts usually form a two-zone structure with a stable inner zone and a highly variable outer zone, which forms and disappears owing to waveparticle interactions on the timescale of a day, and is strongly influenced by the very-low-frequency plasma waves. Recent observations revealed a third radiation zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(197 citation statements)
references
References 20 publications
12
183
2
Order By: Relevance
“…This new ring resulted from a combination of electron losses to the interplanetary medium and scattering by electromagnetic ion cyclotron waves to the Earth's atmosphere (Shprits et al, 2013). Associated to recent observations of Van Allen Probe spacecraft, our results show that the radiation belts are sometimes different from the general feature.…”
Section: Introductionmentioning
confidence: 55%
“…This new ring resulted from a combination of electron losses to the interplanetary medium and scattering by electromagnetic ion cyclotron waves to the Earth's atmosphere (Shprits et al, 2013). Associated to recent observations of Van Allen Probe spacecraft, our results show that the radiation belts are sometimes different from the general feature.…”
Section: Introductionmentioning
confidence: 55%
“…This expansion places the peak of the multi-MeV particles, now recovered in flux levels, inside the plasmasphere. Shprits et al [2013] model a similar situation in which electrons at low L shells find themselves inside the plasmasphere in a very different plasma environment, where electromagnetic ion cyclotron waves are not present and the strongest emissions are whistler mode hiss. That study points out that, in this configuration, energetic and relativistic electrons will resonate with hiss waves near the equator and will be lost to the atmosphere on a time scale of a few days.…”
Section: Discussionmentioning
confidence: 99%
“…Shprits et al (2013) demonstrated that EMIC waves play a crucial role for the dynamics of the ultrarelativistic populations in the radiation belts. Detached proton subauroral arcs are caused by the precipitation of ring current protons into the atmosphere produced by EMIC waves (e.g., Jordanova et al 2007;Spasojevic and Fuselier 2009;Yuan et al 2010).…”
Section: Scattering and Heating Of Particles By Emic Waves In The Prementioning
confidence: 99%